Measuring horizontal integration among health care providers in the community: an examination of a collaborative process within a palliative care network. Issue 3 (May 2015) - Bainbridge, Daryl; Brazil, Kevin; Krueger, Paul; Ploeg, Jenny; Taniguchi, Alan; Darnay, Julie
Abstract In many countries formal or informal palliative care networks (PCNs) have evolved to better integrate community-based services for individuals with a life-limiting illness. We conducted a cross-sectional survey using a customized tool to determine the perceptions of the processes of palliative care delivery reflective of horizontal integration from the perspective of nurses, physicians and allied health professionals working in a PCN, as well as to assess the utility of this tool. The process elements examined were part of a conceptual framework for evaluating integration of a system of care and centred on interprofessional collaboration. We used the Index of Interdisciplinary Collaboration (IIC) as a basis of measurement. The 86 respondents (85% response rate) placed high value on working collaboratively and most reported being part of an interprofessional team. The survey tool showed utility in identifying strengths and gaps in integration across the network and in detecting variability in some factors according to respondent agency affiliation and profession. Specifically, support for interprofessional communication and evaluative activities were viewed as insufficient. Impediments to these aspects of horizontal integration may be reflective of workload constraints, differences in agency operations or an absence of key structural features.